THE INFLUENCE OF AUDIT EXPERIENCE, WORKLOAD, AND TIME PRESSURE ON AUDITOR'S ABILITY TO DETECT FRAUD (Case Study of Auditors who Work at KAP Surabaya) - horri, miftahol; aulia, yoosita (Prodi Akuntansi FEB UNITOMO, 2021)
This study aims to test and analyze the factors that affect the ability of auditors to detect fraud. This research is motivated by the many issues regarding the inability of auditors to detect fraud in carrying out their audit work. Factors that are very important for auditors in detecting fraud are audit experience, workload, and time pressure. Therefore, the problem examined in this study is whether audit experience, workload, and time pressure affect the ability of auditors to detect fraud either partially or simultaneously. The population in this study were all auditors who worked at 43 public accounting firms in the city of Surabaya. The sample in this study was determined using purposive sampling method. The sample selected in this study were 17 KAP where each KAP had 5-8 people who were used as respondents. A total of 74 questionnaires were distributed, but only 57 questionnaires were returned and could be processed. The analysis technique used to test the hypothesis is multiple linear regression analysis. The results showed that audit experience, workload, and time pressure had a positive and significant effect on the ability of auditors to detect fraud either simultaneously or partially.